The Contribution of the Furniture Industry in Sukoharjo Regency and Steps to Facing the Threat of an Economic Recession at the End of the Covid-19 Pandemic Era - Fery wisnu Saputro (Proceeding of International Conference on Science, Health, And Technology, 2022)
Illustration of the economic recession in Indonesia that occurred due to the ongoing pandemic. This is supported by data showing that consumption in several quarters is still minus. This condition is also due to the low purchasing power of the people. As a result of this, it also affects all sectors, including the furniture industry sector, which has also experienced the impact of a decline in purchasing power at both national and international levels with various existing obstacles. One of the furniture industries in Indonesia is located in Sukoharjo Regency. This study aims to determine the contribution of the existing furniture industry and how to anticipate the threat of an economic recession. The data used in this study is secondary data from 2015 to 2020 sourced from the Department of Trade, Cooperatives, Small and Medium Enterprises of Sukoharjo Regency. Data analysis used in this research is contribution analysis. Based on the results of the study, it can be seen that the contribution of the furniture industry in Sukoharjo Regency from 2015 to 2020 fluctuated. In 2015 it was recorded that the contribution given was worth 6.06%, then followed in 2017 it had a contribution value of 7.81 and then decreased until 2020 it reached 5.3 percent. There are five strategic steps in dealing with and anticipating the threat of an economic recession that occurs. One of the steps is to prepare an emergency fund so that it can survive when turnover decreases.